2009
DOI: 10.1007/s00284-009-9533-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Thermostable Esterase from Thermus scotoductus SA-01: Evidence of a New Family of Lipolytic Esterases

Abstract: An esterase, designated EstTs1, was identified and characterized from a genomic library of Thermus scotoductus SA-01 (ATCC 700910). The library was screened in Escherichia coli for lipolytic activity on tributyrin agar plates. A 1.7-kb DNA fragment from a lipolytic positive clone was sequenced and two open reading frames (ORFs) were identified. A 774-bp ORF, designated EstTs1 with an estimated molecular mass of 28.6 kDa, and a 693-bp ORF, designated EstTs2 with an estimated molecular mass of 25.6 kDa, were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…no. ACS36170; 27.5% similarity according to a Needle (EMBOSS) alignment (http://www.ebi.ac.uk/Tools/psa/) [23]]. A common GXSXG motif that occurs in carboxylesterases and lipases was found in both enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…no. ACS36170; 27.5% similarity according to a Needle (EMBOSS) alignment (http://www.ebi.ac.uk/Tools/psa/) [23]]. A common GXSXG motif that occurs in carboxylesterases and lipases was found in both enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, thermostable lipases have been reported in different Thermus isolates [19], [20] and were recently expressed in thermophilic yeasts [21], [22]. A thermostable esterase from Thermus scotoductus has been reported that was partially biochemically characterized [23]. Finally, two thermostable lipases have been reported from Thermosyntropha lipolytica , an anaerobic, thermophilic, alkali-tolerant bacterium that grows syntrophically with methanogens on lipids [24].…”
Section: Introductionmentioning
confidence: 99%
“…While the lipases have the ability to hydrolyse long chain acylglycerols, esterases function by hydrolysing ester substrates with short chain fatty acids. Some examples of bacterial esterases are from Lactobacillus plantarum [20] and Thermus Scotoductus [21].…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of the two positive clones isolated from the library showed that they both contained the locus TT_C0904 encoding the previously characterized 34 kDa esterase that is responsible for the activity [ 62 ]. There is another example with a library constructed in plasmids from the Thermus scotoductus SA-01 genome, which revealed a new enzyme named Est1 and belonging to a new family of lipolytic enzymes, which shares 76% sequence identity with the putative hydrolase of T. thermophilus HB27 WP_011172791 [ 64 ]. However, we did not isolate this putative hydrolase from the functional screening of our library.…”
Section: Lipolytic Enzymes From Thermus Thermophilus mentioning
confidence: 99%